Sistem Penyederhanaan Kepartaian Dalam Konstitusi Negara-Negara Presidensial Multipartai Dan Pengalaman di Indonesia - Tri Lestari, Shinta (Jurnal Konstitusi & Demokrasi, 2023)
This article is to find out the arrangement of political parties in the constitution of several multi-party presidential countries which lead to simplification of the party system to be compared with the simplification of the party system in Indonesia based on experience and design based on four classifications of party simplification related to the electoral system, parliamentary thresholds, coalitions. and the dissolution of political parties. By using normative juridical research methods through secondary data, 79 countries with a presidential system of government were found, 20 of which were multi-party presidential countries whose constitution contained four classifications of party simplification systems. The constitutions of Chile, Georgia and Suriname include electoral systems. The constitutions of Cyprus, Georgia, Mexico and Panama provide for parliamentary thresholds. The constitutions of 14 countries regulate restrictions on activities up to the dissolution of political parties. Indonesia includes provisions that have an impact on simplifying parties in the constitution, namely regarding coalitions and the dissolution of political parties as the authority of the Constitutional Court. The simplification of parties itself is a design determined by the state through restrictions in Article 28J paragraph 2 of the Constitution of the Republic of Indonesia. Although this Article cannot be applied directly as a justification for the simplification of political parties in Indonesia, the spirit or spirit of the 1945 Constitution of the Republic of Indonesia can still be used as justification for the simplification of political parties through four classifications as found in the constitutions of other countries as comparison material for future design decisions. suitable for application in your own country.